Anna Hubbard : out of the shadows - Cunningham, Mia, 1943- (The University Press of Kentucky, 2009)
Anna Eikenhout (1902-1986) was an honors graduate of Ohio State University, a fine-arts librarian, a skilled pianist, and an avid reader in three languages. Harlan Hubbard (1900-1988), a little-known painter and would-be shantyboater, seemed an unlikely husband, but together they lived a life out of the pages of Thoreau's Walden. Much of what is known about the Hubbards comes from Harlan's books and journals. Concerning the seasons and the landscape, his writing was rapturous, yet he was emotionally reticent when discussing human affairs in general or Anna in particular. Yet it was through he.